Health Literacy Improves the Lifestyle of Undergraduate in Education Students (Journal of Education and Development, 2020)
The choices related to lifestyle habits, during the period of graduation at the university are decisive for the development of a healthy lifestyle and for combating the risk behaviors that lead to Chronic Non-communicable Diseases. This study aims to examine the relationship between a discipline focused on health literacy and the development of attitudinal components aimed at the competence of self-care and responsibility of pedagogy students, in relation to the choices that constitute their lifestyle. The investigation of this research indicates that the literacy and health promotion program developed during the Principles of Healthy Living for education students had a positive effect on the development of competence and responsibility for self-care in their lifestyle. Quantitative data were obtained using the socio-demographic questionnaire and validated scale of the Fantastic Lifestyle and the Global Physical Activity Questionnaire, at the beginning and end of the course. The results point to an improvement in lifestyle with an increase in the practice of recreational physical activity of vigorous intensity (p=0.0339) and in its frequency (p=0.0130). Still, there was a significant reduction in the level of physical inactivity (p=0.0451), in addition to the evident improvement in lifestyle (p=0.0196), with all participants grouped in the categories “Good”, “Very Good” and “Excellent” referring to lifestyle. This study showed that an approach to health education for university students is a positive initiative for teaching important skills to consolidate a healthy lifestyle.